ALIH FUNGSI LAHAN SAWAH DI KECAMATAN PURWOREJO, KUTOARJO, DAN PURWODADI KABUPATEN PURWOREJO - Hidayat, Nurul; Mulyanto, Djoko (Universitas Pembangunan Nasional Veteran Yogyakarta, 2024)
Purworejo Regency is one of the districts in Central Java which has experienced conversion of rice fields. Purworejo Regency has an area of 1,034.82 km2. The study was conducted in 3 sub-districts, namely Purworejo District with an area of 52.72 km2, Kutoarjo with an area of 37.59 km2, and Purwodadi District with an area of 53.96 km2. The purpose of the study was to analyze the conversion of rice field land, the suitability of conversion to RTRW, and identify the impact of rice field conversion in Purworejo Regency. The study was conducted by survey method with purposive sampling points. Sample based on the suitability of conversion obtained from overlaying the rice field land conversion map with the RTRW map of Purworejo Regency 2011-2031. The suitability analysis of conversion is based on the land use balance with conformity classes appropriate and non-conforming. The results showed that the 3 sub-districts studied experienced conversion of paddy fields in 2013-2021. The conversion of paddy fields based on the RTRW of Purworejo Regency 2011-2031, Kutoarjo District covers an area of 4.31 ha with a suitability level of 10.07% and not according to 89.93%. In Purworejo sub-district covering an area of 25.38 ha with a suitability level of 26.04% and not according to 73.96%. Purwodadi sub-district covers an area of 12.68 ha with a suitability rate of 4.89% and not conformity of 95.11%. The conversion of paddy fields needs to be controlled so as not to disturb the stability of food security of an area.